Perancangan Tourism Display Board untuk Objek Wisata Pasar Terapung Lok Baintan - Karunia Puji Hastuti; Nevy Farista Aristin; Aswin Nur Saputra; Faisal Arif Setiawan (Universitas Lambung Mangkurat, 2022)
AbstractLok Baintan Floating Market is a leading tourist attraction on a national scale. Completeness of facilities is the main requirement as a support for tourist attractions. The existence of a tourism display that contains information on tourist destinations is very important for tourists. The purpose of the service activity is to provide knowledge about the management of tourism places through the design of information boards Tourism displays provide the information tourists need in tourist attractions. Tourism displays can be information about tourist attractions, such as geographical conditions, history, prices, prohibitions, and warnings in tourist attractions. The limited availability of tourism displays in tourist attractions is caused by several things such as immature planning of tourist attraction, the results of needs analysis that have not listed them, and minimal knowledge of making information boards. The design of tourist information boards is a solution to introduce the culture of tourism promotion. The results of the service showed that 96% of the community felt very satisfied. The design of information boards can be a mobilizer for local people to increase knowledge related to tourism promotion. Keywords: tourism, tourist attractions, tourism display board AbstrakPasar Terapung Lok Baintan merupakan atraksi wisata unggulan berskala nasional. Kelengkapan fasilitas merupakan syarat utama sebagai pendukung atraksi wisata. Keberadaan tourism display yang berisi informasi destinasi wisata sangatlah penting bagi para wisatawan. Tujuan kegiatan pengabdian adalah memberikan pengetahuan mengenai pengelolaan tempat pariwisata melalui perancangan papan informasi. Tourism display menyediakan informasi yang dibutuhkan wisatawan di tempat wisata. Tourism display dapat berupa informasi tentang tempat wisata, seperti kondisi geografi, sejarah, harga, larangan, dan peringatan di tempat wisata. Terbatasnya ketersediaan tourism display di tempat wisata disebabkan oleh beberapa hal seperti belum matangnya perencanaan ruang tata kelola tempat wisata, hasil analisis kebutuhan yang belum mencantumkannya, dan pengetahuan teknis pembuatan papan informasi yang minim. Perancangan papan informasi wisata merupakan solusi untuk mengenalkan budaya promosi wisata. Hasil pengabdian menunjukkan 96% masyarakat merasa sangat puas. Perancangan papan informasi dapat menjadi penggerak masyarakat lokal untuk menambah pengetahuan terkait promosi wisata. Kata kunci: pariwisata, atraksi wisata, papan informasi wisata